Respuesta :

Answer:

1) 43/40

2) 35/6

3) 43/40

4) -5/3

5) 1/6

Step-by-step explanation:

1)  -1 4/5 = -(1*5 +4)/ 5= -9/5

or          1= 5/5  so -1 4/5= -( 5/5+ 4/5)=-9/5

-2 7/8= -(2*8+7)/8=-23/8

=> -9/5 - ( -23/8)= -9/5 + 23/8 = (( -9*8)+(23*5))/40= (-72+ 115)/40

                                                                                =  43/40

2) 4 3/4= (4*4+3)/4= 19/4

-1 1/12= -(1*12+1)/12= -13/12

=> 19/4 - (-13/12)= 19/4 + 13/12 = ((19*3)+13)/12= (57+13)/12= 35/6

3) same like 1)

4) 3 1/3 = (3*3+1)/3= 10/3

=> 10/3 -5= (10- 3*5)/3= (10-15)/3= -5/3

5) -1/3 + 1/2= ((-1*2)+(1*3))/6 = (-2+3)/6= 1/6

ACCESS MORE